Antimicrobial Screening of Siddha Formulation Manosilai Chooranam - Ananthi, V.; Chandraleka, B.; Balamani, S.; Jeylani, M. P. Abdul Kader (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Manosilai chooranam is a Siddha formulation indicated for mainly Naal patta suram(Chronic fever) . This drug was tested for antimicrobial property against E. coli, pseudomonas aeruginosa by agar disc diffusion method and hence the result of In-vitro antimicrobial assay reveals that the formulation Manosilai chooranam (MC) possess significant anti-microbial activity against E-coli, Pseudomonus aeruginosa.
Keywords: Siddha formulation; Anti-microbial activity; Manosilai chooranam